Analisis Program Kebijakan Pencegahan dan Pengendalian Diabetes Melitus di Puskesmas Belik Kabupaten Pemalang - Videa Salsabilla Wijaya; Chatila Maharani (Inovasi Kesehatan Global, 2025)
Diabetes Mellitus (DM) is one of the diseases whose prevalence continues to increase in the world, so it can be said that DM has become a problem that needs attention. Indonesia is in 9th position with a total of 563 million sufferers. Central Java Province recorded 647,093 DM sufferers and in Pemalang Regency, DM is ranked first with a total of 18,579 sufferers at the Belik Health Center in Belik District, Pemalang Regency in 2022. The purpose of this study was to analyze the DM disease prevention and control policy program at the Belik Health Center. The Belik Health Center has 2 DM disease management programs, 2 programs, namely the Posbindu (Integrated Development Post) program and the Prolanis (Chronic Disease Management Program). Method: this study is a study with a qualitative method and a case study approach. Results: This study was conducted by means of in-depth interviews and direct observation to the research site, interviews with key informants and triangulation to obtain information related to services and implementation of DM prevention and control programs in the Belik Health Center area.